Sugar-sweetened beverage intakes among adults between 1990 and 2018 in 185 countries - Laura Lara-Castor; Renata Micha; Frederick Cudhea; Victoria Miller; Peilin Shi; Jianyi Zhang; Julia R. Sharib; Josh Erndt-Marino; Sean B. Cash; Dariush Mozaffarian; Global Dietary Database (Nature Communications, 2023)
Abstract Sugar-sweetened beverages (SSBs) are associated with cardiometabolic diseases and social inequities. For most nations, recent estimates and trends of intake are not available; nor variation by education or urbanicity. We investigated SSB intakes among adults between 1990 and 2018 in 185 countries, stratified subnationally by age, sex, education, and rural/urban residence, using data from the Global Dietary Database. In 2018, mean global SSB intake was 2.7 (8 oz = 248 grams) servings/week (95% UI 2.5-2.9) (range: 0.7 (0.5-1.1) in South Asia to 7.8 (7.1-8.6) in Latin America/Caribbean). Intakes were higher in male vs. female, younger vs. older, more vs. less educated, and urban vs. rural adults. Variations by education and urbanicity were largest in Sub-Saharan Africa. Between 1990 and 2018, SSB intakes increased by +0.37 (+0.29, +0.47), with the largest increase in Sub-Saharan Africa. These findings inform intervention, surveillance, and policy actions worldwide, highlighting the growing problem of SSBs for public health in Sub-Saharan Africa.